Coastlines, Coastal Cities, and Climate Change: A Perspective on Urgent Research Needs in the United States - Sandifer, Paul A.; Scott, Geoffrey I. (Frontiers in Marine Science, 2021)
This paper builds upon and is intended as a companion to Friedman et al. (2020), “Research Priorities for Achieving Healthy Marine Ecosystems and Human Communities in a Changing Climate,” (Front. Mar. Sci. 7:5), but with a more explicit focus on research needed to improve the resilience and survivability of coastal communities as they face existential threats from climate change. And our perspective is also somewhat different, being based on our experiences over a combined nearly 95 years of work in research, management, and policy, much of it related to coastal environments and their communities, rather than expert deliberation within a large group. We present a shorter list of 25 research priorities targeted to coastal communities, some modified slightly and others extensively from recommendations selected from Friedman et al. (2020) and some new. These priorities are intended to help start more discussion of needs with and within communities, help focus research attention on actions that have potential to identify critical decision points and make positive differences for communities. We conclude that priority research should be undertaken with urgency and a much greater level of trans- and interdisciplinary and community-participatory approaches than yet seen.